RACIAL INEEUQALITY AND SEXIST OPPRESSION IN TONI MORRISON'S BELOVED - Amina Rashid; Md. Masud Rana (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
AbstractThis study examines the construction of racialized society and gendered identities in fictional text of Morrison's Beloved. The research aim is to analyze and explore how these identities are constructed in Beloved by using a feminist approach. We find that the imposed ideal of femininity is absorbed and patriarchy is assumed. Female’s black characteristics are repressed both intra-communally and inter-communally. In the former, black female characters are not ‘fitted’ to white femininity as they strive for identity crisis even among the blacks. In the latter, they are whim of male dominance-subject of incest, rape and seduction. Though, women are doubly repressed, it is not the racial discrimination that threatens and jeopardizes black women identity rather a sheer domination of patriarchal power from within and without exaggerating debasing women life among the whites. Therefore, this paper reflects on the manifestation of femininity and patriarchy in a radicalized society and how these two  interact in women life in Morison's Beloved.